2017
DOI: 10.18632/oncotarget.16132
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism at IGF1 locus is associated with anemia

Abstract: In vitro and in vivo studies suggest that IGF-1 has a role in erythropoiesis. There is evidence that the rs35767 C/T polymorphism near IGF1 is associated with plasma IGF-1 levels. We investigated the effect of this polymorphism on hemoglobin (Hb) concentration and anemia. The study group comprised 3286 adult Whites. The rs35767 polymorphism was screened using a TaqMan allelic discrimination assay. The rs35767 polymorphism was not associated with age, gender, BMI, waist circumference, smoking, blood pressure, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We analyzed 2794 unrelated individuals consecutively recruited at the Department of Medical and Surgical Sciences of the University “Magna Graecia” of Catanzaro and at the Department of Systems Medicine of the University of Rome-Tor Vergata as previously described 33 , 34 . The criteria for recruitment were: presence of at least one cardio-metabolic risk factor including but not limited to family history of diabetes, dysglycemia/type 2 diabetes, hypertension, dyslipidemia, and overweight/obesity.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed 2794 unrelated individuals consecutively recruited at the Department of Medical and Surgical Sciences of the University “Magna Graecia” of Catanzaro and at the Department of Systems Medicine of the University of Rome-Tor Vergata as previously described 33 , 34 . The criteria for recruitment were: presence of at least one cardio-metabolic risk factor including but not limited to family history of diabetes, dysglycemia/type 2 diabetes, hypertension, dyslipidemia, and overweight/obesity.…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, some observational clinical studies demonstrated an inverse correlation of blood levels of IGF-1 with Hb and in various populations (elderly, adult, and dialyzed patients) ( Iglesias et al, 1998 ; Nilsson-Ehle et al, 2005 ; Succurro et al, 2011 ). A proof of the direct action of IGF in improving anemia is demonstrated by the association of an IGF genetic polymorphism (related to low IGF concentration) with low Hb levels in a large cohort of adult individuals ( Marini et al, 2017 ).…”
Section: Chronic Inflammation In Advanced Cancer Patientsmentioning
confidence: 99%
“…For instance, Marini et al reported that the individuals carrying rs35767 T allele showed low risk of anemia compared with C allele. [26] A related study carried out among Japanese population demonstrated that rs5742714 polymorphism in combination with overweight could affect development of pancreatic cancer. [27] Among Chinese pregnant women, those carrying GA/AA genotypes were more likely to have spontaneous preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with the relevant studies carried out in other types of human disease. [2628] In addition, strong linkage disequilibrium was observed between polymorphisms rs5742714 and rs972936. Haplotype analysis demonstrated that the haplotype C-T dramatically elevated the susceptibility to ONFH when compared to C-C, while G-T decreased the individual susceptibility to ONFH among Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%